Radiation shielding for a nuclear fusion device with inertial electrostatic confinement - Seung Min Lee; Eduardo Lobo Lustosa Cabral; Helio Yoriyaz (Brazilian Journal of Radiation Sciences)
In an inertial electrostatic confinement nuclear fusion device, IECF, thermal neutron population is created near the neutron shielding that is proportional to the fast neutrons generation rate; nevertheless, this proportionality varies with the experimental arrangement. Thus, to properly measure the fast neutron generation rate by the IECF device it is necessary to previously elaborate a detailed neutron transport model between the IECF device and the radiation shield, where the neutron detector will be located. This model is elaborated using the Monte Carlo N-Particle Code and the same is used to design the required radiation shield for the safe operation of the device.